Peningkatan Kinerja Pemasaran: Media Sosial, Inovasi Produk, dan pemasaran Afiliasi - Amin Kuncoro (BADAN PENERBIT STIEPARI PRESS, 2024)
The aim of the research is to test social media, product innovation and affiliate marketing as mediation. The research design uses quantitative descriptive research and quantitative grounded theory. The research sample was MSMEs in the Religious Tourism area in Kudus Regency, totaling 400 respondents. The research informants are decision makers at religious tourism objects in Kudus Regency. The research results explain that marketing performance has increased due to the increasingly intensive role of social media. Product innovations are increasing in number of items and marketing affiliates are able to mediate, so that marketing performance, especially for MSMEs in Religious Tourism in Kudus Regency, has a dual role, apart from increasing local economic resources, it also contributes to regional original income which is managed by the district government. However, the negative impact of increasing marketing performance is that social urbanism is increasing. This needs to be reviewed again by stakeholders in Kudus Regency.